2011
DOI: 10.5811/westjem.2011.9.6781
|View full text |Cite
|
Sign up to set email alerts
|

Occult Pneumothoraces in Acute Trauma Patients

Abstract: IntroductionMany traumatic pneumothoraces (PTX) are not seen on initial chest radiograph (CR) (occult PTX) but are detected only on computed tomography (CT). Although CR remains the first tool for detecting PTX, most trauma patients with significant thoracoabdominal injuries will receive both CT and CR. The primary objective of this study was to retrospectively determine the effectiveness of CR for detecting PTX in trauma patients. Our hypotheses were that CR is a sensitive indicator of PTX on CT, that chest p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
0
7
1
Order By: Relevance
“…Lee et al [10] reported a higher rate, 22% (8/36) in a center where thoracic CT scans were performed at clinician discretion and in a trauma population of variable severity. This drainage rate even reached 44% (30/68) in another series, but chest tube indications were left at the discretion of the physician [9]. Thus, a large range of prevalence is observed in the literature, mainly due to selection biases with studied populations, strategies of nonsystematic thoracic CT scan, the nondistinguishing of mechanical ventilation, or wide difference between the indications of drainage.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Lee et al [10] reported a higher rate, 22% (8/36) in a center where thoracic CT scans were performed at clinician discretion and in a trauma population of variable severity. This drainage rate even reached 44% (30/68) in another series, but chest tube indications were left at the discretion of the physician [9]. Thus, a large range of prevalence is observed in the literature, mainly due to selection biases with studied populations, strategies of nonsystematic thoracic CT scan, the nondistinguishing of mechanical ventilation, or wide difference between the indications of drainage.…”
Section: Discussionmentioning
confidence: 91%
“…This is probably due to continuing improvements in imaging techniques these last years and to our policy of systematic whole-body CT scans of patients with severe trauma [24,25]. Although OPTXs are not visible on chest x-ray, some require an emergent drainage or a change of the initial management strategy [8,9]; Guerrero-López et al [8] had thus found that 18% of patients (19/104) admitted to a trauma intensive care unit who had a CT scan had an OPTX requiring chest tube insertion during their management. Lee et al [10] reported a higher rate, 22% (8/36) in a center where thoracic CT scans were performed at clinician discretion and in a trauma population of variable severity.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Although there is sufficient evidence to advocate a conservative approach in these patients [19], the underlying pathophysiology is likely to differ from traumatic Pneumothorax [20]. Occult pneumothorax, on the otherhand, specifically describes the entity where chest x-ray is considered normal, but CT scan of the chest reveals evidence of a pneumothorax [21]. Several studies on the management of traumatic pneumothorax often include patients with occult pneumothorax as part of their cohort and, this substantially weakens their generalizability [22] [23].…”
Section: Discussionmentioning
confidence: 99%